The Effect of Students’ Cultural Values on Social Stigmatization of Alcohol Use Disorder - Zıvdır Yeşilyurt, Pelin (Addicta: The Turkish Journal on Addictions, 2024)
The aim of this study was to examine the effect of students’ cultural values on their social stigmatization of alcohol use disorder. This study is descriptive and correlational. The sample of the study consisted of 250 female and male stu- dents enrolled in the Vocational School of Health Services in the 2023–2024 academic year. Descriptive Characteristics Information Form, Individual Culture Values Scale and Social Stigma Scale for Alcohol Use Disorder were used to collect the data. Descriptive statistics (number, percentage distributions), one-way ANOVA test, independent t-test, and Pearson correlation analysis were used to evaluate the data.Among the participants, 76.8% were female, 37.2% were 21 years of age or older, 57.6% were first-year students, and 40.8% were first and emergency aid students. The mean score of the Social Stigma Scale for Alcohol Use Disorder was 75.55 ± 19.18 (min: 20–max: 100), and the mean score of the Individual Cultural Values Scale was 79.79 ± 17.47 (min: 26–max: 130). It was determined that there was a significant and positive correlation between the total scores obtained from the Individual Culture Values and Social Stigmatization of Alcohol Use Disorder Scale and all its sub-dimensions (p < .01; r: 0.353).It was determined that students with high mean social stigma toward alcohol use disorder also had high mean cultural values.
Keywords: Addiction to alcohol; cultural values; relationship between cultural values and alcohol addiction; university students